Polycyclic aromatic hydrocarbon removal from subsurface soil mediated by bacteria and archaea under methanogenic conditions: Performance and mechanisms. (15th November 2022) - Gou, Yaling; Song, Yun; Yang, Sucai; Yang, Yan; Cheng, Yanan; Li, Jiabin; Zhang, Tengfei; Cheng, Yanjun; Wang, Hongqi
Abstract: In situ anoxic bioremediation is an easy-to-use technology to remediate polycyclic aromatic hydrocarbon (PAH)-contaminated soil. Degradation of PAHs mediated by soil bacteria and archaea using CO2 as the electron acceptor is an important process for eliminating PAHs under methanogenic conditions; however, knowledge of the performance and mechanisms involved is poorly unveiled. In this study, the effectiveness and efficiency of NaHCO3 (CO2 ) as an electron acceptor to stimulate the degradation of PAHs by bacteria and archaea in highly contaminated soil were investigated. The results showed that CO2 addition (EC2000) promoted PAH degradation compared to soil without added CO2 (EC0), with 4.18%, 9.01%–8.05%, and 6.19%–12.45% increases for 2-, 3- and 4-ring PAHs after 250 days of incubation, respectively. Soil bacterial abundances increased with increasing incubation time, especially for EC2000 (2.90 × 10 8 g −1 soil higher than EC0, p < 0.05). Different succession patterns of the soil bacterial and archaeal communities during PAH degradation were observed. According to the PCoA and ANOSIM results, the soil bacterial communities were greatly (ANOSIM: R = 0.7232, P = 0.001) impacted by electron acceptors, whereas significant differences in the archaeal communities were not observed (ANOSIM: R = 0.553, P = 0.001). Soil bacterial and archaeal co-occurrence network analyses showed that positive correlations outnumbered the negative correlations throughout the incubation period for both treatments (e.g., EC0 and EC2000), suggesting the prevalence of coexistence/cooperation within and between these two domains rather than competition. The higher complexity, connectance, edge, and node numbers in EC2000 revealed stronger linkage and a more stable co-occurrence network compared to EC0. The results of this study could improve the knowledge on the removal of PAHs and the responses of soil bacteria and archaea to CO2 application, as well as a scientific basis for the in situ anoxic bioremediation of PAH-contaminated industrial sites. Graphical abstract: Image 1 Highlights: The synergism of bacteria and archaea promoted PAH degradation after CO2 addition. The soil bacterial and archaeal communities changed greatly and slightly after CO2 addition, respectively. Electron acceptors changed the microbial networks, were more complex and stable in EC2000. The mutualistic relationships within and between domains exceed competition throughout incubation.